Two new Australian fungus-feeding thrips in two new Plectrothripini genera (Thysanoptera, Phlaeothripinae) - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2017)
Two new genera are erected of plectrothripine Phlaeothripidae from northern Australia, each based on a single species. One has a long stout projection ventrally on the second antennal segment, the other has a unique arrangement of the dorsal facets of the compound eyes. In both of them the thoracic ventral sclerites are extensively eroded.